2018
DOI: 10.1007/s10140-018-1579-x
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasonographic “whirlpool sign” in testicular torsion: valuable tool or waste of valuable time? A systematic review and meta-analysis

Abstract: The WS, when correctly diagnosed, may be viewed as a very definitive sign for TT in the pediatric and adult populations. However, its role in neonates is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…Ultrasound is an effective imageological diagnosis and has been widely used (Ota et al, ). Besides, the positive whirlpool sign (WS) in ultrasonography was considered as a very definitive sign for TT among paediatric and adult patients (McDowall et al, ). Recently, magnetic resonance imaging (MRI) with minimum apparent diffusion coefficient (ADC) values can be used as an auxiliary examination in the diagnosis of partial TT (Beyazal et al, ; Ufuk, Herek, Herek, & Akbulut, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is an effective imageological diagnosis and has been widely used (Ota et al, ). Besides, the positive whirlpool sign (WS) in ultrasonography was considered as a very definitive sign for TT among paediatric and adult patients (McDowall et al, ). Recently, magnetic resonance imaging (MRI) with minimum apparent diffusion coefficient (ADC) values can be used as an auxiliary examination in the diagnosis of partial TT (Beyazal et al, ; Ufuk, Herek, Herek, & Akbulut, ).…”
Section: Discussionmentioning
confidence: 99%
“…36 A recent meta-analysis to determine the accuracy of the whirlpool sign observed a pooled sensitivity of 92% (95% CI, 0.70-0.98), a pooled specificity of 99% (95% CI, 0.95-1.00) and a summary estimate log odds ratio of 5.32 (95% CI, 1.59-9.05; p=0.001) in adults and nonneonatal pediatric patients. 37 Another sign that may be visualized on ultrasonography is the redundant spermatic cord sign, where the spermatic cord appears torturous, indicating an abnormality in the attachment of the tunica vaginalis. 27 In the setting of an acute scrotum, this sign may be seen as a boggy pseudo mass or a torsion knot (Figure 2).…”
Section: Ultrasonographymentioning
confidence: 99%
“…44 From the 16 articles included, 12 concluded that the US WS is a valuable tool in the diagnosis of IV, while the remaining four 12,17,23,25 concluded that the sign was of limited value. 48 The pooled sensitivity of the US WS in diagnosing IV of 87.42% (95% CI: 81.05-92.25) from the nine studies that were included in the meta-analysis is less than ideal. They further reported that the WS was noted in some individuals without volvulus (10 patients with intestinal obstruction from post-surgical adhesions and one patient with mesenteric lymphadenopathy secondary to leukaemia).…”
Section: Discussionmentioning
confidence: 98%
“…45 Other pathological conditions where the WS has also been described include omental torsion 46 enteritis, megacolon, 44 ovarian torsion 47 and testicular torsion. 48 The pooled sensitivity of the US WS in diagnosing IV of 87.42% (95% CI: 81.05-92.25) from the nine studies that were included in the meta-analysis is less than ideal. Hence, other diagnostic modalities must be considered when the sign is absent.…”
Section: Discussionmentioning
confidence: 98%